Information in relationship of exchange - V. D. Kuligin (Вестник университета)
Arguments, justifying the specificity of information in the relations of exchange, have been presented. The interpretation of information, as the values of the things to be exchanged, has been given. The content of the ideal, which carries information about the value, has been considered. A subjective moment in value has been examined, which is the form, in which information has been clothed. The creative aspect of entrepreneurship, which is connected with the hidden and previously unknown perspectives and means of making a profit, has been highlighted. The connection between individual information, actions of market actors and price fluctuations has been traced.